ROLE OF PROFESSIONAL IDENTITY IN SELF-REALIZATION OF PSYCHOLOGISTS-TEACHERS - S I Kudinov; Yu V Vladimirova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article highlights the problem of the role of professional identity in self-realization of psychologists- teachers. Within the frame of a system-defined approach the research identifies and describes the individual- typological features of the phenomena interesting to us. The works that focus on the study of self-realization are subjected to the analysis, as the result it is noted that in this field there are still gaps in the understanding of this issue. Thus, the study from the perspective of the influence of professional identity on the successful self-realization of the personality is recognized as relevant. In the framework of this study the following assumptions are put forward: there is a relationship between the professional identity and successful self- realization of the personality; the level of formation of professional identity has an impact on the success of personality self-realization; the professional identity not fully formed acts as a barrier for creativity, activity, internality and constructive self- realization; fully formed professional identity provides a high success rate of self-realization. The purpose of this study was to investigate the features of self- realization and professional identity of psychologists-teachers. For the study, we used "Multidimensional questionnaire of personality self-realization" (MQPS) by S.I. Kudinov, for the study of professional identity the following methods were used: "Professional identity-marginalism" questionnaire by E.P. Ermolaeva and Methods of measuring professional identity (MMPI) by L.B. Schneider. The results obtained were subjected to quantitative analysis. In the article the author relies on the data gathered as a result of a study conducted at the Institute of Education Development of the Republic of Bashkortostan (GAOU DPO IRO RB), city of Ufa. The sample consisted of 142 educational psychologists. As a result of the conducted research, the specific relationship between the professional identity and self-actualization of the educational psychologists was established